Radiation oncology peer review in Australia and New Zealand. Issue 2 (3rd March 2022) - Chin, Stephen; Or, Michelle; Ong, Wee Loon; Millar, Jeremy; Chilkuri, Madhavi; Vinod, Shalini
Summary: Peer review is a part of high quality care within radiation oncology, designed to achieve the best outcomes for patients. We discuss the importance of and evidence for peer review in clinical practice. The Royal Australia and New Zealand College of Radiologists (RANZCR) has evolved a Peer Review Assessment Tool (PRAT) since 1999. We report the results of a RANZCR faculty survey conducted in radiation oncology facilities across Australia and New Zealand to guide the 2019 PRAT revision process, and discuss the development and implementation of the 2019 PRAT. Peer‐review processes are now mandated as a component of Australian and International Quality Standards. Several practical recommendations might address challenges for effective implementation of peer review process in routine clinical practice. This includes prioritising tumour sites and treatment techniques for peer review within the time and resources constraints of each institution, improving resource allocation, ensuring optimal timing and duration for peer review meetings, and adopting multi‐centre virtual peer review meeting where necessary.